1996
DOI: 10.1524/ract.1996.75.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Determinations of Uranium Structures by EXAFS: Schoepite and Other U(VI) Oxide Precipitates

Abstract: We have investigated the structures of U(VI) oxides precipitated from room temperature aqueous solutions at low ionic strength as a function of pH. Using the uranium Lm-edge extended Xray absorption fine structure (EXAFS) and infrared (IR) spectroscopies as probes of the local structure around the uranium, a trend is observed whereby the axial oxygen bond lengths from the uranyl groups increase from 1.80 A at pH = 7 to 1.86 A at pH = 11. Shifts in the IR spectral frequencies support this assignment. A concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
43
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 33 publications
19
43
0
Order By: Relevance
“…A similar peak has been reported by others in many U(VI) samples [46,50]. The peak has been attributed to multiple scattering.…”
Section: Incorporation Of Cerium Into Nickel Oxide Filmssupporting
confidence: 88%
“…A similar peak has been reported by others in many U(VI) samples [46,50]. The peak has been attributed to multiple scattering.…”
Section: Incorporation Of Cerium Into Nickel Oxide Filmssupporting
confidence: 88%
“…The k 2 -weighted chi data were Fourier-transformed to yield R-space or pseudo Radial Distribution Function (RDF) plots as in SAYERS and BUNKER (1988). A amplitude reduction factor of 0.9 was used, which is within the range (0.8 to 1.0) typically used for U (BARGAR et al, 2000;THOMPSON et al, 1997;ALLEN et al, 1996). Simulated EXAFS spectra were also generated based on the documented crystallographic properties for U in schoepite (FINCH et al, 1997) using ab initio based theory, using FEFF 7.2 (MUSTRE de LEON et al, 1991;REHR et al, 1991;1992;REHR and ALBERS, 1990;STERN et al, 1995).…”
Section: Exafs Data Analysesmentioning
confidence: 99%
“…However, the frequency of these peaks is known to shift to lower frequencies under certain conditions such as for uranyl-containing solids with high stoichiometric Na to U ratios (e.g., clarkieite, CEJKA, 1999, and references therein). FT-IR studies with schoepite-containing solids from aqueous suspensions that have been equilibrated at pH values of 7, 9 and 11, show that the ν 3 peak, which is associated with the asymmetric stretch of the linear [O=U=O] 2+ group moves to a lower frequency of vibration at high pH conditions (from 910 cm -1 to 865 cm -1 ) (ALLEN et al, 1996). Uranium-EXAFS studies with these high pH samples indicated that the uranyl group O's in these systems may have been located at longer radial distances than that of the U in suspensions that were equilibrated at lower pH values and that bridging of the equatorial O's may have occurred (ALLEN et al, 1996, and references therein; see TABLE 1).…”
Section: Ft-ir Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 This is because schoepite has so many U-U distances and due to destructive interference from so many U-U interactions, the FT spectra tend to be fairly structureless in the 3 to 4 Å region. …”
Section: Uranium Fourier-transformed Data For the 2h-evaporator Scalementioning
confidence: 99%